Updated Chronology of the Last Deglaciation in the Făgăraş Mts (Romania) - Zoltán Kern; Petru Urdea; Mircea Ardelean; ASTER Team; Zsófia Ruszkiczay-Rüdiger (Geosciences)
So far, published geochronological data poorly constrain the Late Pleistocene glacial fluctuations in the Făgăraş Mts (Southern Carpathians, Romania). The deglaciation chronology in the central Făgăraş Mts is supported by new (n = 5) and recalculated (n = 5) 10Be exposure ages from a southern and two northern valleys. Cosmic ray exposure (CRE) ages were calculated considering the effects of surface denudation, uplift and snow-shielding. A 10Be exposure age obtained from a glacial landform representing the last glacierets of the central Făgăraş Mts yielded an age of 13.3 ± 1.2 ka. A polished bedrock sample and a moraine boulder constrain the age of a cirque glacier stage to 14.5 ± 1.5 ka, while quite coherent CRE ages from two erratic boulders place the previous stage at ~18.7 ka (18.6 ± 1.7 ka and 18.7 ± 1.7 ka). These glacial stages coincide with major deglaciation stages M4 and M2a reconstructed in the Retezat Mts, derived from comparable CRE ages calculated using the same methodology; however, geomorphological and/or geochronological evidence of the intermediate stages is still not found in the central Făgăraş Mts. All CRE ages gathered from the landforms corresponding to the more extended glacial stages are younger than expected from their morphostratigraphic position and thus considered as minimum age constraints. However, considering the coherent CRE ages of the above morphostratigraphic stage, it is likely that the balanced-budget glaciological conditions corresponding to these more extended stages prevailed before ~19 ka and likely coincided with the cold peaks of the Marine Isotope Stage 2. The currently available in situ 10Be data do not support the existence of a period of glacier advance during the Holocene or Greenland Stadial-1 (Younger Dryas) in the central Făgăraş Mts.